Pengaruh pemberian isi rumen sapi terhadap kualitas fisik dan kimia UMB (Urea Molasses Block): The effect of feeding cow rumen contents on the physical and chemical quality of UMB (Urea Molasses Block) - Hidayati, Nurul; Riszqina, Riszqina; Agustina, Desi K. (Fakultas Peternakan Universitas Papua, 2024)
Abstract Urea Molasses Block (UMB) is a supplement feed for ruminants, in solid form which is rich in nutrients. The contents of the rumen can potentially be used as an additional ingredient for the manufacture of supplements in ruminants. However, the quality of the rumen content supplements produced still needs to be studied. Therefore, the purpose of this study was to determine the nutritional content of urea molasses blocks fed with bovine rumen contents at several concentrations and without bovine rumen contents. This study used a completely randomized design (CRD) with 4 treatments, namely P0: UMB without rumen content, P1: UMB + 10% rumen content, P2: UMB + 20% rumen content, and P3: UMB + 30% rumen content, respectively treatment there were 3 replications. Based on the results of statistical analysis, it can be concluded that the addition of cow's rumen content to Urea Molasses Block (UMB) at various concentrations can affect the physical and chemical qualities of UMB. The more addition of rumen contents as a mixture of Urea Molasses Block (UMB), the higher the crude protein, crude fiber, crude fat and water content but the lower the dry matter. The treatment with the best results was P3 (UMB + 30% rumen content) with a crude protein value of 12.11%, 18.87% crude fiber, 8.92% crude fat, and 67.78% dry matter. Keywords: Feed for ruminan; Nutrient content; Urea molasses block Abstrak Urea Molases Block (UMB) adalah pakan suplemen untuk ternak ruminansia, berbentuk padat yang kaya dengan zat-zat makanan. Isi rumen berpotensi dapat dijadikan bahan tambahan untuk pembuatan suplemen pada ternak ruminansia. Namun kualitas suplemen isi rumen yang dihasilkan masih perlu untuk dikaji. Oleh karena itu, tujuan dari penelitian ini untuk mengetahui kandungan nutrisi urea molases blok yang diberi isi rumen sapipada beberapa konsentrasi dan tanpa isi rumen sapi. Penelitian ini menggunakan Rancangan Acak Lengkap (RAL) dengan 4 perlakuan yaitu P0: UMB tanpaisi rumen, P1: UMB + 10% isi rumen, P2: UMB + 20% isi rumen, dan P3: UMB + 30% isi rumen, masing –masing perlakuan terdapat 3 ulangan. Berdasarkan hasil analisis statistik dapat disimpulkan bahwa penambahan isi rumen sapi terhadap Urea Molasses Block (UMB) pada berbagai konsentrasi dapat berpengaruh terhadap kualitas fisik dan kualitas kimia UMB. Semakin banyak penambahan isi rumen sebagai bahan campuran Urea Molasses Block (UMB) maka kandungan protein kasar, serat kasar, lemak kasar dan kadar air semakin tinggi tetapi bahan kering semakin rendah. Perlakuan yang memiliki hasil terbaik adalah P3 (UMB + 30% isi rumen) dengan nilai protein kasar 12,11%, serat kasar 18,87%, lemak kasar 8,92%, dan bahan kering 67,78%. Kata kunci: Kandungan nutrisi; Pakan ruminansia; Urea molasses block